Young Corn Ear Addition Improves Some Nutrients and Lowering Glycemic Index of Chiffon Cake - Wan Rosli, W. I.; Che Mohd Zin, Che Anis Jauharah; Sathyasurya, Daniel Robert (Scientific Research Publishing Inc, 2014)
The effects of partial replacement of wheat flour with young corn ear (YCE) on sensory properties and glycemic index (GI) of chiffon cake were investigated. Dried YCE was processed into powdered form and added in chiffon cake formulations to replace wheat flour partially at concentrations of 0 (control), 10%, 20% and 30%. Protein, ash and dietary fibre contents of chiffon cake added with YCE powder were increased in line with the levels of YCE used. Even though protein content of YCE-based cakes increased in line (13.3% to 15.7%) with the levels of YCE (10% to 30%), but there was no significant difference compared to control. Sensory evaluation results indicate that partial replacement of wheat flour with up to 10% is satisfactory as compared to other levels of wheat flour replacement. Interestingly, addition of YCE at 10% to partially replace wheat flour resulted in reduction of postprandial blood glucose response. The GI value for chiffon cake added with YCE was 49 lower than control cake which recorded GI value at 60. In conclusion, novel food ingredient of YCE can be incorporated in selected bakery products to enhance nutritional composition while at the same time help in reducing the GI value. Further investigation on the addition of YCE into other bakery products in relation to nutrition and glycemic response effects can also be explored.